2019
DOI: 10.1101/520783
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Retapamulin-assisted ribosome profiling reveals the alternative bacterial proteome

Abstract: The use of alternative translation initiation sites enables production of more than one protein from a single gene, thereby expanding cellular proteome. Although several such examples have been serendipitously found in bacteria, genome-wide mapping of alternative translation start sites has been unattainable. We found that the antibiotic retapamulin specifically arrests initiating ribosomes at start codons of the genes. Retapamulin-enhanced Ribo-seq analysis (Ribo-RET) not only allowed mapping of conventional … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
132
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(137 citation statements)
references
References 116 publications
4
132
1
Order By: Relevance
“…As shown here, translated smORFs are more prevalent than previously believed and are found in contexts that would be difficult to distinguish by other methods, including bioinformatics approaches that have been successfully employed previously (16,17). While traditional ribosome profiling can guide the prediction (53,54) or, in conjunction with experiments to verify protein synthesis, even support the annotation of intergenic smORFs in bacteria (27), ribosome profiling with stalled initiation complexes allows for new ORFs to be located in contexts that are generally-ignored, including within or overlapping other genes as shown here and by the group of Vázquez-Laslop and Mankin (35). These new, internal altORFs may represent a new class of functional and regulatory proteins that comprise an ever-expanding proteome.…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…As shown here, translated smORFs are more prevalent than previously believed and are found in contexts that would be difficult to distinguish by other methods, including bioinformatics approaches that have been successfully employed previously (16,17). While traditional ribosome profiling can guide the prediction (53,54) or, in conjunction with experiments to verify protein synthesis, even support the annotation of intergenic smORFs in bacteria (27), ribosome profiling with stalled initiation complexes allows for new ORFs to be located in contexts that are generally-ignored, including within or overlapping other genes as shown here and by the group of Vázquez-Laslop and Mankin (35). These new, internal altORFs may represent a new class of functional and regulatory proteins that comprise an ever-expanding proteome.…”
Section: Discussionmentioning
confidence: 88%
“…Ribosome profiling signals for Onc112 and retapamulin are slightly different. A recent study used retapamulin and ribosome profiling to identify sites of non-canonical initiation within annotated ORFs (35). Like Onc112, retapamulin traps newly initiated 70S ribosomes at start codons while allowing elongating ribosomes to complete protein synthesis, such that ribosome density is strongly enriched at start codons ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…TSS identification with harringtonine (HHT) ribosome profiling libraries was done using previously published custom python scripts that were modified for our purposes (26,27). Identification of novel TSS and smORFs was done as previously published (26,27) with the following changes: (a) rpkm was calculated for each TSS peak in both the HHT and no challenge library, (b) the TSS peak rpkm were >5-fold enriched in HHT compared to no challenge, and (c) the ORF rpkm were >5-fold enriched in no challenge compared to HHT. Identification of known TSS, internal TSS (iTSS), and N-terminal extensions was done as previously published using density files assigned to the 3'-end of reads and adjusted for the P-site (15 nt offset) (26).…”
Section: Ncbi and Ucsc)mentioning
confidence: 99%
“…Recently developed 379 methods like dRNA-seq (Sharma et al, 2010) and Cappable-seq (Ettwiller et al, 2016) 380 identified hundreds of transcription start sites antisense to annotated genes producing 381 antisense transcripts with unknown translation status and function. Modern ribosome profiling 382techniques, including stalling ribosomes at translation initiation sites, identified several 383 unambiguous start codons for protein coding genes which overlap with annotated genes 384 either in sense or in antisense direction(Meydan et al, 2019, Weaver et al, 2019. We 385 suggest that these 'abnormal' transcriptional and translational signals in next generation 386 sequencing analysis should not be neglected but analyzed in more detail as has been 387 conducted for the long overlapping gene pop, since many novel functions, especially for 388 pathogenicity of novel hosts or survival in new niches, might be 'hiding' in the genome of any 389 strains and plasmids 395All oligonucleotides, bacterial strains and plasmids used or created in this study are listed in 396…”
mentioning
confidence: 99%